Perbandingan Handwashing Promotion dengan Metode Bernyanyi dan Handwashing Dance terhadap Pengetahuan Teknik Mencuci Tangan Anak Usia Prasekolah - Gusti Ayu Ratih Kurniasari; Made Rini Damayanti; Made Pasek Kardiwinata (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2016)
The World Health Organization (WHO) in 2012 there are 11 States that the cause of death of children aged under five years in Indonesia, where diarrhea was ranked eighth. In Indonesia, diarrhea claimed the lives of about 6% of the total number of children in Indonesia. The most important thing in diarrheal disease management is preventive efforts. In delivering health promotion for children of preschool age, it takes interesting and interactive methods such as singing method and handwashing dance. This research aims to know the handwashing promotion comparison with singing method and handwashing dance of handwashing techniques knowledge in preschool-aged children. This research uses a type of quantitative research design experimental research or quasy experiment through the Nonequivalent Control Group Design. A large sample of 74 people (38 person group singing method, 36 people group handwashing dance) were selected for a total sampling with inclusion and exclusion criteria. Data collection by using the observation sheets hand washing techniques. Based on nonparametric Mann-Whitney test in mind that the value of Asymp. Sig (2-tailed) results under the 0.05 so that there is a meaningful difference between the increase in handwashing techniques knowledgewithsinging method and handwashing dance, while the average value of an increased score before and after intervention handwashing dance is higher compared to the singing methods namely 54,71 with 21.20. Then it can be inferred that the handwashing intervention dance more effective in improving knowledge of the techniques of hand washing in preschool-aged children in PAUD TK Pra Widyalaya Gurukula and PAUD Negeri Pembina Bangli.